Psychiatric and non-psychiatric polypharmacy among older adults with schizophrenia: Trends from a population-based study between 2000 and 2016 - Lunghi, Carlotta; Rochette, Louis; Massamba, Victoria; Tardif, Isabelle; Ouali, Amina; Sirois, Caroline (Frontiers in Pharmacology, 2023)
Background Schizophrenia is a severe psychiatric disorder associated with multiple psychiatric and non-psychiatric comorbidities. As adults with schizophrenia age, they may use many medications, i.e., have polypharmacy. While psychiatric polypharmacy is well documented, little is known about global polypharmacy trends and patterns. This study aimed to draw a portrait of polypharmacy among older adults with schizophrenia from 2000 to 2016. Methods This population-based cohort study was made using the data of the Quebec Integrated Chronic Disease Surveillance System of the National Institute of Public Health of Quebec to characterize recent trends and patterns of medication use according to age and sex. We identified all Quebec residents over 65 years with an ICD-9 or ICD-10 diagnosis of schizophrenia between 2000-2016. We calculated the total number of medications used by every individual each year and the age-standardized proportion of individuals with polypharmacy, as defined by the usage of 5+, 10+, 15+, and 20+ different medications yearly. We identified the clinical and socio-demographic factors associated with polypharmacy using robust Poisson regression models considering the correlation of the responses between subjects and analyzed trends in the prevalence of different degrees of polypharmacy. Results From 2000 to 2016, the median number of medications consumed yearly rose from 8 in 2000 to 11 in 2016. The age-standardized proportion of people exposed to different degrees of polypharmacy also increased from 2000 to 2016: 5+ drugs: 76.6% to 89.3%; 10+ drugs: 36.9% to 62.2%; 15+: 13.3% to 34.4%; 20+: 3.9% to 14.4%. Non-antipsychotic drugs essentially drove the rise in polypharmacy since the number of antipsychotics remained stable (mean number of antipsychotics consumed: 1.51 in 2000 vs. 1.67 in 2016). In the multivariate regression, one of the main clinically significant factor associated with polypharmacy was the number of comorbidities (e.g., Polypharmacy-10+: RR[2 VS 0-1]=1.4; 99% IC:1.3-1.4, RR[3-4]=1.7 (1.7-1.8); RR[5+]=2.1 (2.1-2.2); Polypharmacy-15+: RR[2 VS 0-1]=1.6; 99% IC:1.5-1.7, RR[3-4]=2.5 (2.3-2.7); RR[5+]=4.1 (3.8-4.5). Conclusions There was a noticeable increase in polypharmacy exposure among older adults with schizophrenia in recent years, mainly driven by non-antipsychotic medications. This raises concerns about the growing risks of adverse effects and drug-drug interactions in this vulnerable population.